Understanding the diffusion of non-evidence-based health interventions: The role of experiential evidence. (June 2017) - Evans, Rhiannon; Murphy, Simon; Scourfield, Jonathan; Turley, Ruth
Objective: The utilisation of evidence-based health interventions remains a challenge in educational settings. Although driving forward the scientific evidence-base may contribute to the diffusion of such approaches, abstract notions of population-level impact may not be seen as priorities in local. This paper considers the alternative forms of evidence that inform schools' decision-making in relation to the adoption and implementation of health programmes. Design: Pragmatic formative process evaluation of a non-evidence-based social and emotional learning intervention, the Student Assistance Program, was conducted. Case-study methodology was used. Setting: Cases comprised four socio-economically contrasting secondary schools (free school meal eligibility ranging from 11.3% to 36%). Method: Semi-structured interviews were conducted with 15 programme stakeholders. Results: The results explore (a) how school staff acquired belief in the merit of the Student Assistance Program through an intervention training course; (b) how experiential evidence gained in this course is used in the effort to secure intervention adoption; and (c) how intervention implementation may be limited by the lack of opportunities to develop experiential evidence within the educational setting. Conclusion: Alternative forms of evidence, specifically experiential evidence, are of importance in the diffusion of interventions within educational settings. Evidence-based approaches need to further acknowledge and accommodate these alternative forms of understanding to enhance their uptake and implementation.